SETTING FREE THE KITES - George, Alex, 1970-, author (New York : G.P. Putnam's Sons, 2017)
"For Robert Carter, life in his coastal Maine hometown is comfortably predictable. But in 1976, on his first day of eighth grade, he meets Nathan Tilly, who changes everything. Nathan is confident, fearless, impetuous--and fascinated by kites and flying. Robert and Nathan's budding friendship is forged in the crucible of two family tragedies, and as the boys struggle to come to terms with loss, they take summer jobs at the local rundown amusement park. It's there that Nathan's boundless capacity for optimism threatens to overwhelm them both, and where they learn some harsh truths about family, desire, and revenge."